BUILDING AN EFFECTIVE STRATEGY FOR THE FINANCIAL DEVELOPMENT OF TERRITORIAL COMMUNITIES - Dzhuryk, Khrystyna; Kashchyshyn, Vasyl (European Science, 2023)
The strategy for the development of territorial communities is a plan that takes time and includes strategic and operational goals and mechanisms for their implementation, as well as the strategy determines the priorities of the development of the commun